The organizational climate and its effect on the academic planning of the Faculty of Economic Sciences of the University of Tumbes 2017 (SCIÉNDO INGENIUM, 2021)
The non-experimental type of research with a descriptive-correlational design. 55 teachers from the Faculty of Economics were surveyed and 55% of the total rated the organizational climate as good, 62% gave the same qualification for Academic Planning. 53% highlighted that they always had autonomy to carry out their work; 49% who almost always participated in the academic department meetings; 56% say that they have almost never had a reward for a job well done and 53% say that they have almost never received recognition for an extra effort. It should be noted that 71% are willing to work full time. With respect to Academic Planning, 67% state that the study plan is almost always designed according to current regulations according to the needs of the labor market. 33% expressed that almost always the syllable is elaborated according to the competences contemplated in the curricular plan and is elaborated in a coordinated way with colleagues. In conclusion, there is a direct correlation between organizational climate and academic planning, considering that the Pearson correlation coefficient was 0.519 with a degree of significance lower than the P-value